UPAYA GURU TAHSIN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS 1 DI MDTA DAURUN NUR - Zaki Almuttaqi (Wahdatul Ulum Institute, 2022)
One of the schools in Medan, North Sumatra, has a program on tahsin al-Quran. Currently, tahsin al-Quran has been widely carried out in various schools in the city of Medan, including MDTA Daurun Nur. School children at MDTA Daurun Nur are equipped with an understanding of tahsin al-Quran from an early age so that it becomes the forerunner of their understanding in the future. Therefore, the author wants to find out how the efforts of tahsin teachers in improving the ability to read the Koran at the Daurun Nur MDTA school. In this case the author uses field research (field research) where the data is obtained from the field. In this case, the author explores the information obtained at MDTA Daurun Nur. So it was found that the teachers had motivated the students and also provided teaching about the Koran so that the reading of MDTA Daurun Nur students in the future would get better. Keywords: Effort, Tahsin, MDTA Daurun Nur Abstrak Salah satu sekolah di Medan Sumatera Utara ada program tentang tahsin al-Quran, tahsin al Quran saat sekarang ini sudah banyak sekali dilakukan di bernagai sekolah di Kota Medan termasuk MDTA Daurun Nur. Anak-anak sekolah di MDTA Daurun Nur dibekali pemahaman tahsin al-Quran sudah dari sejak dini agar menjadi cikal-bakal pemahaman mereka untuk kedepannya. Oleh karena itu penulis ingin mencari tahu bagaimana upaya guru tahsin dalam meningkatkan kemampuan membaca al Quran di sekolah MDTA Daurun Nur. Dalam hal ini penulis menggunakan penelitian lapangan (field research) yang mana datanya di dapatkan dari lapangan. Dalam hal ini penulis menggali informasi yang di dapatkan di MDTA Daurun Nur. Maka ditemukan bahwasannya para guru sudah melakukan motivasi kepada para siswa dan juga memberikan pengajaran tentang al-Quran agar bacaan siswa didik MDTA Daurun Nur kedepan semakin membaik. Kata Kunci: Upaya, Tahsin, MDTA Daurun Nur